Socio-cultural values, economic development and political stability as correlates of trust in the European Union - Rimac, Ivan; Štulhofer, Aleksandar (2004)
This paper provides a comparative empirical analysis of social values in Croatia, the European Union (EU), the countries joining in the first round, and a group of European countries outside the EU. Following up on the analysis of the data obtained in international research into European values carried out at the end of the 90’ s on national samples of most European countries, the authors have endeavoured to determine the differences in the spread of post-material values and the scope of social capital. The objective is to define where, in terms of social values, Croatia is currently located, and thus to sketch out its readiness or lack of readiness for joining the EU. In the second part, the paper offers a comparative analysis of factors that affect the level of public confidence in the EU.
Projekt MZOS
ENG